EXTENSIVE AND INTENSIVE READING APPROACHES IN TEACHING ENGLISH READING - TAEMBO, MAULID (ALENA : Journal of Elementary Education, 2023)
This paper describes the conceptual base of extensive and intensive reading approaches in teaching English reading. The description and illustration come from various sources, experiences, and references. Discussion of the topic is based on the results of interpretation and theoretical studies, which are then combined with the results of previous research and observation in teaching English reading. It hopes become as one of useful information about a comparative study between extensive and intensive reading approaches for the teachers, particularly for the English teachers and as one of the reference for the further researchers who want to conduct a research about extensive and intensive reading approaches. Both extensive and intensive reading can increases word meaning knowledge and produce gain in topical and word knowledge. The approaches have different motivation in reading and same phases with different strategies or techniques. They have a significant effect to students’ English competence growth. However, intensive reading offers refer to the careful reading or translation of shorter, more difficult foreign language text, while extensive reading is generally associated with reading large amounts with the aim of getting an overall understanding of the material.